A comparative X-ray diffraction study of ferroelectric thin films and superlattices. (17th February 2017) - Tikhonov, Yu. A.; Zakharchenko, I. N.; Razumnaya, A. G.; Yuzyuk, Y. I.; Pavunny, Sh.; Ortega, N.; Kumar, A.; Katiyar, R. S.
ABSTRACT: A number of ferroelectric thin films with various barium concentration and two sets of superlattices with different composition and number of constituent layers were investigated using X-ray diffraction. Out-of-plane unit cell parameters, values of microstrains, and sizes of coherent scattering regions were determined. Modulation period for superlattices was also calculated. We discuss the structural features of the samples.